Wine and heart health: learning from the French paradox - Opie, Lionel H.; Lamont, Kim; Lecour, Sandrine (SA Heart Journal, 2017)
Wine with good food (albeit fatty) is an integral part of the French dietary pattern which is often called the French paradox. We note that among the inherent compounds in wine, especially red, that could confer cardioprotection, are resveratrol and melatonin. However, we do not think that drinking red wine is the sole explanation for the French paradox, whereby a rich high fat diet is associated with a lower than expected incidence of coronary heart disease. Rather, we note differences in French social behaviour – French eating is for refined pleasure and conviviality. ''Food is bought, cooked, and celebrated.'' Gardening with the availability and love of fresh vegetables is common. This lifestyle may be the key to the French paradox which, however, seems to be a passing phenomenon as dietary patterns and passion for gardening change even in France. Recent data suggest that, after all, the French are susceptible to the same rules as are other nations. The true Mediterranean diet pattern, found only in the relatively small geographic part of the South of France, is by contrast low in fat, with little red meat and rich in fish and olive oil. Like the French diet, it emphasises fresh fruit and vegetables and includes modest wine with the meals.